LABA BERSIH, ARUS KAS OPERASI, DAN DIVIDEN KAS: BUKTI EMPIRIS PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK BEI - Nita Sintiani; Riani Tanjung (LAND JOURNAL, 2026)
The transportation and logistics sector is a key driver of Indonesia’s economic recovery, particularly in the post-pandemic period when the flow of goods and public mobility have intensified. Nevertheless, the distribution of cash dividends within this sector does not always align with the levels of net income and operating cash flow. According to financial theory, net income represents a firm’s overall financial performance, whereas operating cash flow reflects the availability of liquid funds for dividend payments. This study examines the influence of net income and operating cash flow on cash dividends in 17 transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2023-2024 period. The research adopts an associative quantitative approach using secondary data derived from published financial statements. Data analysis includes normality testing, correlation analysis, multiple linear regression, partial t-tests, simultaneous F-tests, and coefficient of determination analysis. The findings indicate that net income has a significant partial effect on cash dividends, while operating cash flow does not show a significant partial effect. However, both variables jointly exert a significant influence on cash dividend distribution.